Investigation of thermal characteristic of eutectic fatty acid/damar gum as a composite phase change material (CPCM) - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Silakhori M.; Ong H.C. (Springer Verlag, 2023)
Binary mixtures; Chemical reactions; Chemical stability; Differential scanning calorimetry; Eutectics; Fatty acids; Heat storage; Phase change materials; Porous materials; Thermoanalysis; Thermodynamic properties; Thermodynamic stability; Composite phase change materials; Eutectic mixture; Fourier transform infra reds; Myristic acid; Thermal analyzers; Thermal characteristics; Thermal Performance; Thermal conductivity